A pilot clinical trial to explore the effects of UV exposure on vitamin D synthesis and inflammatory responses in vitamin D-Deficient adults - Chaodeng Mo; Johny Bajgai; Md. Habibur Rahman; Soonchul Choe; Sofian Abdul-Nasir; Hui Ma; Wenjing He; Thu Thao Pham; Haiyang Zhang; Goh Seong Hoon; Kim Bomi; Cheol-Su Kim; et al. (Scientific Reports)
Abstract Ultraviolet radiation (UVR) is essential for vitamin D synthesis and influences various biological processes. This study examined the effects of controlled UV exposure on vitamin D synthesis and skin inflammation in healthy adults. In a randomized clinical trial, 24 volunteers received four 5-min standardized UV exposures (UVB: 1.34 mW/cm²; UVA: 27.7 mW/cm²) on representative skin areas. Blood samples were collected before exposure and after every two sessions to assess serum vitamin D, inflammatory markers, vitamin D-related markers, and oxidative stress indicators. Serum vitamin D concentration significantly increased after four exposures (p < 0.001), while calcium, phosphorus, and parathyroid hormone (PTH) significantly decreased (p < 0.05). Reactive oxygen species (ROS) significantly increased (p < 0.001), but no significant changes were observed in nitric oxide (NO) or myeloperoxidase (MPO) levels. Similarly, inflammatory markers such as C-reactive protein (CRP), MPO, and antioxidant enzymes (glutathione peroxidase [GPx] and catalase [CAT], showed no significant alterations. Among the inflammatory cytokines assessed, interleukin (IL)-1β levels showed a slight increase without reaching significance, and the levels of other cytokines such as IL-6, IL-10, tumor necrosis factor-alpha (TNF-α), and interferon-gamma (IFN-γ) showed no marked alterations. In addition, post-exposure skin assessment revealed no adverse effects. Our findings demonstrate that UVR exposure can enhance vitamin D synthesis in healthy adults without significant inflammatory responses or adverse effects, providing a basis for optimizing UV-based interventions to improve vitamin D status through risk management.